Recent Advances in the Synthesis of Heterocycles via Gold-catalyzed Cascade Reactions: A Review - Gao, Feng; Zhou, Yu; Liu, Hong (Current Organic Chemistry, 2017)
Background: Heterocyclic scaffolds widely occur in natural products and pharmaceutical molecules and because of their broad biological activities, the synthesis of such frameworks with diverse approaches is one of the most attractive fields in modern organic chemistry. Recently, cascade reactions catalyzed by transition metals made astounding advances in the synthesis of heterocyclic compounds for their step economy. Among them, gold-catalyzed cascade reactions emerged as important tools to construct complicated heterocyclic architecture from simple precursors in the past decade. Objective: This review presents an overview of recent advances in gold-catalyzed cascade reactions to generate diverse heterocyclic scaffolds and its applications in total synthesis of natural products.
Keywords: tandem reactions